Bone support correlation of X-Ray and CT for a new PE-glenoid - Bülhoff, Matthias; Sonntag, Nikolai; Trefzer, Raphael; Hirt, Bernhard; Jäger, Sebastian; Schonhoff, Mareike; Renkawitz, Tobias; Kasten, Philip (Archives of orthopaedic and trauma surgery, 2024)
The radiographic evaluation of novel cementless anatomic polyethylene (PE) glenoid components featuring a titanium-coated back is still unclear. This study explores potential radiolucent lines (RLL) between the radiopaque titanium layer and sclerotic convex reamed bone in an intermodal comparison analysis with computed tomography (CT) scans.